Numerical modeling of pile penetration in silica sands considering the effect of grain breakage - Jin, Yin-Fu; Yin, Zhen-Yu; Wu, Ze-Xiang; Daouadji, Ali (Finite elements in analysis and design, 2018)
Current numerical platforms rarely consider the effect of grain breakage in the design of sandy soil foundations. This paper presents an enhanced platform for large deformation analyses which considers the effect of grain breakage during pile penetration in silica sand. For this purpose, a model based on critical state theory has been developed within the framework of multisurface plasticity to account in the same constitutive platform the effect of stress dilatancy and particle fragmentation. Furthermore, to implement the underlying constitutive equations into a finite element code, a stress integration scheme has been adopted by extending a cutting plane algorithm to the model with multiple yielding mechanisms. A laboratory model test and a series of centrifuge tests of pile penetration are simulated to verify the performance of the selected constitutive approach in terms of pile resistance and grain breakage distribution, with the parameters of sand calibrated through a set of drained triaxial compression tests from low to very high confining pressure. Some extra features of the enhanced platform are also discussed, such as: i) the effect of sand crushability on pile resistance and ii) the nonlinear relation of pile resistance to sand density. The proposed findings demonstrate the capability of this numerical platform to proper design of pile foundation in sandy soils and highlight the interplay between stress dilatancy and grain breakage mechanisms during pile penetration processes. •The stress integration of a double-yield-surface model accounting for grain breakage is proposed.•An enhanced simulation platform considering the effect of grain breakage during the pile penetration is established.•The effect of sand crushability to pile resistance by parametric analysis is discussed.•A more accurate nonlinear pile resistance versus density of sand is proposed.